The nature of justice in the decision of the judge of the serang district court from the perspective of the philosophy of law - Putu Bagus Satya Nugraha; I Nyoman Bagiastra (Journal of Law Science, 2024)
The nature of justice is a fundamental principle in the legal system and has great significance in legal philosophy. To know what justice is, there needs to be self-reflection on the awareness that we do not live alone in this world, so that we are led not to neglect our responsibilities to others. Justice in the philosophy of law pays attention to all aspects of the terminology of justice and philosophy of law. Justice is the ideal and purpose of law that reaches the area of legal philosophy by providing the perspective that justice is realized through law. By examining the opinions of several great philosophers, such as Plato and Aristotle, as the foundations of justice, the author attempts to determine the nature of justice in legal philosophy and its application to judges' decisions in judicial processes in Indonesia, especially in the case of two coolies in the Serang District Court. The basic values of justice included in the study of legal philosophy are answered by the philosophy of law itself. Justice is balanced and harmonious in both formal and material laws. The law must hold fast to the essence of justice and moral strength because without justice and morality, the law will lose its supremacy and independent characteristics and will have a major impact in the form of instability in society.